LEGAL PROGRESSIVENESS TOWARDS THE RIGHTS OF VICTIMS OF SEXUAL VIOLENCE - Febi Karina; Nurini Aprilianda; Lucky Endrawati (PT. Radja Intercontinental Publishing, 2026)
Legal protection for victims of sexual violence is a crucial element in a modern criminal justice system focused on substantive justice and victim recovery. Law Number 12 of 2022 concerning Sexual Violence Crimes has introduced the strengthening of victims' rights through restitution mechanisms and the Victim Assistance Fund as a form of accountability for perpetrators and the state. However, in criminal justice practice, problems persist when requests for restitution are not submitted by investigators or public prosecutors, thus limiting judges' ability to fulfill victims' rights. This study aims to analyze the rights and authorities of law enforcement officers in submitting restitution requests and to examine the mechanisms and procedural law for fulfilling victims' restitution rights that are not submitted in court. The research method used is normative legal research with a statutory and conceptual approach. The results show that although the normative framework for restitution is regulated in the TPKS Law and Government Regulation Number 29 of 2025, the procedural law is still not comprehensive. However, Supreme Court Regulation Number 1 of 2022 provides space for an active and progressive role for judges in ensuring the fulfillment of victims' restitution rights. This research emphasizes the urgency of harmonizing regulations and strengthening the role of the state in the recovery of victims of sexual violence.